Preliminary phytochemical analysis and biological evaluation of four medicinal Chinese plant extracts against Tribolium castaneum - Mokhtar, Mokhtar Mohamedalamin; Li, Jianfeng; Du, Zhiping; Cheng, Fangqin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Application of botanical pesticides is a new trend in pest control nowadays as an environmentally safe alternative measures for synthetic chemicals. Hence, this study was aimed to analyze the phytochemical constituents of four medicinal Chinese plants, namely Lonicera maackii, Platycladus orientalis, Viburnum opulus, and Crataegus pinnatifida, and to investigate the insecticidal potentialities of leaves extracts of these plants against Tribolium castaneum. The research was carried out under laboratory conditions, at the Institute of Resources and Environmental Engineering, Shanxi University, China. Ethyl acetate, methanol and water extracts of the plant leaves were tested at different concentrations (5, 2.5, and 1.25% w/v). Yields of extracting materials, mortality and repellent effects were the important parameters evaluated. The phytochemical screening showed the presence of alkaloids, saponins, tannins, flavonoid, and terpenoids in C. pinnatifida, but the other plants contain some of these compounds. The highest ethyl acetate extract concentration (5%) of V. opulus and C. pinnatifida obtained the best mortality means (5.00±0.41 and 4.75±0.25a, respectively), compared to the other treatments, but without significant differences from the middle concentration (2.5%) of both extracts. In repellency test, L. maackii methanol achieved the highest repellency percentage (91.38%). The findings proved that ethyl acetate extract of V. opulus and C. pinnatifida are the best insecticidal treatment, whereas methanol extract of L. maackii is the best repellent effect, against T. castaneum. These three plants require additional studies to be assessed as a component in pest management of store pests.